(9x+4)-(-9x+8)=

Simple and best practice solution for (9x+4)-(-9x+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x+4)-(-9x+8)= equation:


Simplifying
(9x + 4) + -1(-9x + 8) = 0

Reorder the terms:
(4 + 9x) + -1(-9x + 8) = 0

Remove parenthesis around (4 + 9x)
4 + 9x + -1(-9x + 8) = 0

Reorder the terms:
4 + 9x + -1(8 + -9x) = 0
4 + 9x + (8 * -1 + -9x * -1) = 0
4 + 9x + (-8 + 9x) = 0

Reorder the terms:
4 + -8 + 9x + 9x = 0

Combine like terms: 4 + -8 = -4
-4 + 9x + 9x = 0

Combine like terms: 9x + 9x = 18x
-4 + 18x = 0

Solving
-4 + 18x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 18x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 18x = 0 + 4
18x = 0 + 4

Combine like terms: 0 + 4 = 4
18x = 4

Divide each side by '18'.
x = 0.2222222222

Simplifying
x = 0.2222222222

See similar equations:

| 77/11(5-3) | | 2[x+6]=2[-x+6.5] | | 4x+5=3x-14 | | x(4+3)=5-8x | | -4a=14a-12[4a+10] | | (x+7)(5)=45 | | -3[2u+5]+3.5u=-1u | | 100-50/5•10 | | f(7)=8x-3 | | 2b^2-9b-45=0 | | -7+8[5-3s]=3[7-9s] | | 4g+3[g-2]=-5[g-4]-g | | N/18=6/8 | | 0=×-9/x^2-81 | | 2b+4[b-6]=-2[2b-14]+98 | | 5x-7+x=3 | | 8x=540 | | 1/6[6w-12]=6-2[w-2] | | 4x=540 | | 19p+q-6p+8q= | | 2/5c-12=-32 | | 1/6[6w-12]=6-2[w-2 | | 8yt+x=3y+9x-5xy | | 49t^2=100 | | 3x+7z=21 | | 4m-[8-m]=6-2m | | 11r=9r | | 4u-7=u+3[4+u] | | 2/3h-4-2/3h-3=2/3h-6 | | (13x)+(11y)=212 | | 2/3h-4_2/3h-3=2/3h-6 | | x-.2x=523 |

Equations solver categories